PERTANGGUNG JAWABAN PIDANA SEORANG DOKTER DALAM TINDAKAN PEMBEDAHAN - T. Vaison Siahaan (to-ra, 2018)
Abstract The doctor’s profession is noble in the midst of people’s lives. A doctor in his work is directly related to the efforts of healing and suffering of patients. So that not a few people who are resigned to the doctor, even though the doctor because of the actions of medical services he did harm his side. On the other hand, as a result of increasing public legal awareness, including their rights and obligations in the eld of health services, it is not uncommon for a doctor at the green table to take responsibility for his actions. Such responsibilities can be either civil or criminal. Keywords: doctor; healing and suffering; medical services; criminal.